Averting Opioid-induced Respiratory Depression without Affecting Analgesia. (May 2018) - Dahan, Albert; van der Schrier, Rutger; Smith, Terry; Aarts, Leon; van Velzen, Monique; Niesters, Marieke
Abstract : The ventilatory control system is highly vulnerable to exogenous administered opioid analgesics. Particularly respiratory depression is a potentially lethal complication that may occur when opioids are overdosed or consumed in combination with other depressants such as sleep medication or alcohol. Fatalities occur in acute and chronic pain patients on opioid therapy and individuals that abuse prescription or illicit opioids for their hedonistic pleasure. One important strategy to mitigate opioid-induced respiratory depression is cotreatment with nonopioid respiratory stimulants. Effective stimulants prevent respiratory depression without affecting the analgesic opioid response. Several pharmaceutical classes of nonopioid respiratory stimulants are currently under investigation. The majority acts at sites within the brainstem respiratory network including drugs that act at α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (ampakines), 5-hydroxytryptamine receptor agonists, phospodiesterase-4 inhibitors, D1 -dopamine receptor agonists, the endogenous peptide glycyl-glutamine, and thyrotropin-releasing hormone. Others act peripherally at potassium channels expressed on oxygen-sensing cells of the carotid bodies, such as doxapram and GAL021 (Galleon Pharmaceuticals Corp., USA). In this review we critically appraise the efficacy of these agents. We conclude that none of the experimental drugs are adequate for therapeutic use in opioid-induced respiratory depression and all need further study of efficacy and toxicity. All discussed drugs, however, do highlight potential mechanisms of action and possible templates for further study and development. Abstract : Effective respiratory stimulants prevent opioid-induced respiratory depression without affecting the analgesic opioid response. Here the authors discuss drugs acting within the brainstem respiratory network and those acting at the carotid bodies.